Synthesis of Pyrimidine and Pyran Derivatives with the Related Systems and the Study of Their Behavior in the Liquid Solutions. (9th July 2019) - El‐Sayed, Refat; Katouah, Hanadi A.
Abstract : This study aims to synthesis of condensed and non‐condensed heterocyclic rings with long fatty chains as surface active biological compounds. 2‐Cyano‐3‐(dimethylamino)‐ N ‐octadecylacrylamide (5 ) was used to synthesize pyrimidine, pyran, and other condensed products by interacting with appropriate chemical reagents. These compounds were transferred to nonionic surface‐active agents by condensation with propylene oxide. The surface and biological properties showed that these compounds have a high solubility that helps them in easy absorption and adsorption with other compounds. In addition, they have a high ability to decrease the surface tension of the liquids, good wetting, and emulsification power, which can be used at different temperatures without losing their surface or biological properties and enable them for use in industrial and pharmaceutical purposes easily. Abstract :